2012
DOI: 10.2147/ijn.s30428
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioavailability and efficiency of curcumin for the treatment of asthma by its formulation in solid lipid nanoparticles

Abstract: Curcumin has shown considerable pharmacological activity, including anti-inflammatory, but its poor bioavailability and rapid metabolization have limited its application. The purpose of the present study was to formulate curcumin-solid lipid n anoparticles (curcumin-SLNs) to improve its therapeutic efficacy in an ovalbumin (OVA)-induced allergic rat model of asthma. A solvent injection method was used to prepare the curcumin-SLNs. Physiochemical properties of curcumin-SLNs were characterized, and release exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(82 citation statements)
references
References 46 publications
9
73
0
Order By: Relevance
“…The concentration of Cur in the serum of Cur-NPs-and CurNPs-APgp-treated mice was more prolonged than with free Cur. This may be due to the inherent properties of NPs, which may prevent the rapid metabolism of Cur, provide a sustained release, and change the drug pharmacokinetics to improve efficacy (Manjunath and Venkateswarlu, 2005;Wang et al, 2012). These results were consistent with our previous ex vivo data from a Cur-releasing assay, which showed a sustained and prolonged release of Cur in the buffer for up to 10 days (Punfa et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The concentration of Cur in the serum of Cur-NPs-and CurNPs-APgp-treated mice was more prolonged than with free Cur. This may be due to the inherent properties of NPs, which may prevent the rapid metabolism of Cur, provide a sustained release, and change the drug pharmacokinetics to improve efficacy (Manjunath and Venkateswarlu, 2005;Wang et al, 2012). These results were consistent with our previous ex vivo data from a Cur-releasing assay, which showed a sustained and prolonged release of Cur in the buffer for up to 10 days (Punfa et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…This is because PCS is used for hydrodynamic diameter determination, while TEM is used for characterization of particles in the dried state. 27 In vitro antioxidant activities of folic acid-lDh…”
Section: Results and Discussion Preparation And Characterization Of Fmentioning
confidence: 99%
“…Delivery of lipophilic natural compounds by SLNs is a promising strategy that has attracted the attention of both phytochemist and pharmaceutical scientist to overcome their poor solubility, and to increase their pharmaceutical behaviors. In this context, fabrication of various active natural compounds such as acetylshikonin (Eskandani & Nazemiyeh, 2014), curcumin (Wang et al, 2012), frankincense and myrrh essential oils (Shi et al, 2012), tetrandrine (Li et al, 2006), and andrographolide (Parveen et al, 2013) in SLNs have been reported until now. Apparently, however, no investigation has been made to deliver galbanic acid (GBA) to the cancerous cells by the SLNs until now.…”
Section: Introductionmentioning
confidence: 99%